HUBUNGAN FAKTOR PSIKOLOGIS DENGAN RISIKO BUNUH DIRI PADA REMAJA SMA DAN SMK DI BANGLI DAN KLUNGKUNG - Ni Kadek Diah Widiastiti Kusumayanti; Kadek Eka Swedarma; Putu Oka Yuli Nurhesti (Coping: Community of Publishing in Nursing, 2020)
Suicide are currently increasing throughout the world including in Indonesia and it makes suicide become the second leading cause of death at the age of 15 to 29 years old. The cause of suicide cannot be exactly identified. However, there are several factors contribute to suicide such as psychology, biology, family, environment, and sexual orientation. This study aimed at analyzing the correlation among psychological factors (hopelessness, depression, anxiety and stress) with suicide risk in senior and vocational high school adolescents in Bangli and Klungkung Regency. Population in this study was senior and vocational high school adolescents in Bangli and Klungkung whose ages ranging from 15 to 18 years. The sampling technique applied in this research was Non Probability Sampling with Purposive Sampling technique. The instruments used in this study were standard questionnaires named Beck Hopelessness Scale, Depression Anxiety and Stress Scale, and Scale of Suicide Ideation. The results of this study showed p <0.001. It means that there is a meaningful relationship between psychological factors and suicide risk in senior and vocational high school adolescents in Bangli and Klungkung. Moreover, it has a positive correlation which means that the more psychological factors are, the more suicide risk will be. Furthermore, the less psychological factors, the less its risk of suicide will be. Lastly, the strength of the correlation among variables is found weak.